Transcranial magnetic stimulation and ketamine: implications for combined treatment in depression - Dębowska, Weronika; Więdłocha, Magdalena; Dębowska, Marta; Kownacka, Zuzanna; Marcinowicz, Piotr; Szulc, Agata (Frontiers in Neuroscience, 2023)
Drug-resistant mental disorders, particularly treatment-resistant depression, pose a significant medical and social problem. To address this challenge, modern psychiatry is constantly exploring the use of novel treatment methods, including biological treatments, such as transcranial magnetic stimulation (TMS), and novel rapid-acting antidepressants, such as ketamine. While both TMS and ketamine demonstrate high effectiveness in reducing the severity of depressive symptoms, some patients still do not achieve the desired improvement. Recent literature suggests that combining these two methods may yield even stronger and longer-lasting results. This review aims to consolidate knowledge in this area and elucidate the potential mechanisms of action underlying the increased efficacy of combined treatment, which would provide a foundation for the development and optimization of future treatment protocols.